hubungan antara tipe kepribadian big five dengan tingkat kesehatan mental di era media sosial - Erisa Nurul; Tristiardi Ardi Ardani (Jurnal Konseling dan Psikologi Indonesia, 2026)
This study aims to analyze the relationship between Big Five personality traits and the level of mental health among university students who are active social media users. Using a literature review approach, this research examines various empirical findings concerning the influence of personality traits on digital behavior and psychological well-being. The findings indicate that neuroticism is positively correlated with higher risks of mental health issues such as anxiety, stress, and depression, primarily due to social comparison and dependence on online validation. Conversely, conscientiousness and agreeableness serve as protective factors that help individuals maintain emotional balance and manage social media use in a healthy manner. Furthermore, narcissistic tendencies are shown to exacerbate the negative effects of social media on mental health, particularly through excessive pursuit of validation and idealized self-presentation. Enhancing digital literacy and self-awareness is therefore essential for students to engage in productive and balanced digital behavior.